Self-sealing sizing material composition, self-sealing sizing material, and preparation method and application of self-sealing sizing material

By using specific components and processes in the self-sealing rubber compound to build a physical cross-linked network structure, it solves the processing difficulties, pollution and temperature resistance problems of the existing self-sealing tire rubber compound, and achieves higher safety and environmental protection. sex.

CN119331318APending Publication Date: 2025-01-21SAILUN GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411613385.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The self-sealing rubber of existing self-sealing tires has difficulty in mixing and processing, components that pollute the environment, poor high and low temperature resistance and easy flow when the temperature is high, resulting in driving safety hazards.

Method used

A self-sealing rubber composition is provided, including natural rubber, nitrile rubber, rare earth butadiene rubber, thermoplastic elastomer, nano-silica rods, silane coupling agent and modified ethylene-ethyl acrylate copolymer compatibilizer , through specific component ratios and technological processes, a physical cross-linked network structure is constructed to improve the processability and air tightness of the rubber compound.

Benefits of technology

It improves the high and low temperature resistance and processability of the self-sealing rubber, reduces the amount of vulcanizing agent and vulcanizing accelerator, reduces environmental pollution, ensures that the tire can quickly self-seal after being punctured by foreign matter, and prevents air leakage and Flat tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131532600000021
    Figure BDA0005131532600000021
  • Figure BDA0005131532600000071
    Figure BDA0005131532600000071
  • Figure BDA0005131532600000141
    Figure BDA0005131532600000141
Patent Text Reader

Abstract

The invention provides a self-sealing rubber material composition, a self-sealing rubber material, and a preparation method and application thereof. The self-sealing rubber composition comprises first rubber, second rubber, third rubber, a thermoplastic elastomer, nano silicon dioxide rods, a silane coupling agent and a compatilizer, wherein the first rubber is selected from natural rubber and / or polyisoprene rubber, the second rubber is nitrile rubber, and the third rubber is rare earth butadiene rubber; the compatilizer is a modified ethylene-ethyl acrylate copolymer, and the modified ethylene-ethyl acrylate copolymer is obtained by reacting a first styrene-isoprene-styrene block copolymer and maleic anhydride with an ethylene-ethyl acrylate copolymer under the action of an initiator; and the thermoplastic elastomer is a second styrene-isoprene-styrene block copolymer. The self-sealing rubber material prepared from the self-sealing rubber material composition has good stability, and can inhibit the self-sealing rubber material from flowing at high temperature or under high-speed rotation of a tire, so that the driving safety of an automobile is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of rubber technology, in particular to a self-sealing rubber composition, a self-sealing rubber, a preparation method and application thereof. Background Art

[0002] As the only important part of a car that contacts the ground, the tire provides the force required for the vehicle to travel. Its quality and performance are directly related to the life safety of passengers. With the continuous improvement of people's awareness of driving safety, the market demand for safety tires is expanding. After being punctured by foreign objects, ordinary tires will first leak air, then the sidewalls will collapse, and the tire beads will be separated from the rim, which will cause the vehicle to be unable to continue driving or even overturn. However, after being punctured, the safety tire will not leak air or leak air very slowly, and it can still maintain the driving profile and keep the tire beads fixed on the rim, thereby ensuring that the car can travel stably for a long time or temporarily. After the car is equipped with a safety tire, it can not only improve the safety performance, but also eliminate the need to carry a spare tire.

[0003] In the current safety tire technology, run-flat tires (also known as explosion-proof tires) can safely travel about 80 km at a normal speed (such as 80 km / h) when they are deflated or leaking. The sidewall support rubber of the run-flat tire is its key component. The support rubber is hard, which improves the sidewall strength and enables it to flex and deform when deflated to buffer the impact of the road and bear the weight of the car itself. However, run-flat tires have disadvantages such as high noise and poor comfort, so the driver's subjective experience is poor in actual vehicle tests.

[0004] The new generation of self-sealing tires avoids the disadvantages of run-flat tires, such as poor comfort and high noise, and can meet the needs of electric vehicles without spare tires, energy saving, and noise reduction. The characteristic of self-sealing safety tires is that when the driving surface is punctured by sharp objects such as steel nails with a diameter of no more than 6mm, the self-sealing glue on the inner wall of the tire can instantly wrap the hole in all directions to prevent gas leakage in the tire. When the sharp object is pulled out, the sealing layer material will reset and close automatically under the action of the gas pressure in the tire, and completely block the hole, inhibiting the slow leakage of the tire. It eliminates the need for repairs and maintenance, and also avoids the occurrence of tire blowout accidents to a certain extent, thus playing a protective role. Self-sealing safety tires are quick and easy to manufacture, and will not excessively increase the mass of the tire. Self-sealing rubber is an important part of self-sealing safety tires. Self-sealing rubber has good creep fluidity and is very different from the solid form of conventional rubber in appearance. It is generally composed of a variety of polymer materials and has certain viscosity, shrinkage toughness and elasticity.

[0005] The prior art (publication number CN113631647A) discloses a sealant rubber composition for the inner surface of a tire and a sealant coated tire, wherein the sealant rubber composition comprises 100 parts of butyl rubber; 0.5 to 10 parts of benzoyl peroxide; 2 to 5 parts of at least one vulcanization accelerator selected from thiazole, thiuram and dithiocarbamate, 2 to 2.5 parts of a cross-linking agent quinone dioxime compound; more than 100 parts of liquid polybutene; 40 to 50 parts of carbon black; and 5 to 20 parts of a plasticizer. However, the self-sealing composition mainly composed of butyl rubber and organic peroxide has a high requirement for the degree of safety protection of the equipment environment when it is used, due to the high price of butyl rubber and the slow vulcanization speed, and the high price of peroxide and its flammability and explosion. As a result, the cost of storage, transportation and use of the material increases. At present, most of the self-sealing agent products for self-sealing tires on the market still have problems such as difficulty in mixing and processing, easy to produce unnecessary adhesion with equipment or workers during manufacturing and use, the presence of ingredients that pollute the environment in the formula, limited operating temperature, poor high and low temperature resistance, and easy to flow at high temperature or high speed, posing a safety hazard to vehicle driving.

[0006] In summary, researching and developing a self-sealing rubber composition, a self-sealing rubber and a preparation method thereof which have strong processability, are not prone to flow inside the tire due to local heat accumulation, have a wide operating temperature range and are green and environmentally friendly are of great significance to improving the safety performance of tires. Summary of the invention

[0007] The main purpose of the present invention is to provide a self-sealing rubber composition, a self-sealing rubber, a preparation method and application thereof, so as to solve the problems in the prior art that the self-sealing rubber of the self-sealing tire has difficulty in mixing and processing, there are components in the formula that pollute the environment, the self-sealing rubber has poor high and low temperature resistance, and it is easy to flow at high temperature, causing hidden dangers to driving safety.

[0008] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a self-sealing rubber composition, which comprises: a first rubber, a second rubber, a third rubber, a thermoplastic elastomer, a nano-silica rod, a silane coupling agent and a compatibilizer; wherein the first rubber is selected from natural rubber and / or polyisoprene rubber, the second rubber is nitrile rubber, and the third rubber is rare earth butadiene rubber; the compatibilizer is a modified ethylene-ethyl acrylate copolymer, and the modified ethylene-ethyl acrylate copolymer is obtained by reacting a first styrene-isoprene-styrene block copolymer, maleic anhydride and ethylene-ethyl acrylate copolymer under the action of an initiator; and the thermoplastic elastomer is a second styrene-isoprene-styrene block copolymer.

[0009] Further, the self-sealing rubber composition comprises: 20 to 50 parts of the first rubber, 20 to 50 parts of the second rubber, 20 to 50 parts of the third rubber, 10 to 30 parts of a thermoplastic elastomer, 5 to 20 parts of nano-silica rods, 1 to 10 parts of a silane coupling agent and 5 to 15 parts of a compatibilizer; preferably, by weight, the self-sealing rubber composition comprises: 30 to 50 parts of the first rubber, 20 to 30 parts of the second rubber, 20 to 30 parts of the third rubber, 10 to 20 parts of a thermoplastic elastomer, 15 to 20 parts of nano-silica rods, 1 to 5 parts of a silane coupling agent and 5 to 10 parts of a compatibilizer.

[0010] Furthermore, the ethylene-ethyl acrylate copolymer has a structure shown in formula (I):

[0011]

[0012] Among them, R 1 Selected from vinylene, propenylene or C 2 ~C 6 A straight chain alkylene group; R 2 Selected from C 2 ~C 5 x is any integer between 10 and 30, and y is any integer between 10 and 30.

[0013] Furthermore, in the compatibilizer, the corresponding segment of the first styrene-isoprene-styrene block copolymer includes a first styrene repeating unit and a first isoprene repeating unit, and preferably the weight ratio of the first styrene repeating unit to the first isoprene repeating unit is (10-50):(50-90), and more preferably the weight average molecular weight of the corresponding segment of the first styrene-isoprene-styrene block copolymer in the compatibilizer is 25,000-28,000; preferably, in the compatibilizer, the grafting rate of the corresponding segment of the first styrene-isoprene-styrene block copolymer is 40-60wt%, and the grafting rate of the corresponding grafting group of maleic anhydride is 40-60wt%; preferably, the weight ratio of ethylene-ethyl acrylate copolymer, the first styrene-isoprene-styrene block copolymer, maleic anhydride and initiator is (95-120):(32-62):(1-9):(3-13).

[0014] Furthermore, the second styrene-isoprene-styrene block copolymer in the thermoplastic elastomer comprises a second styrene repeating unit and a second isoprene repeating unit, and preferably the weight ratio of the second styrene repeating unit to the second isoprene repeating unit is (10-40):(60-90); preferably, the weight average molecular weight of the thermoplastic elastomer is 80,000-120,000; preferably, the thermoplastic elastomer is selected from one or more of SIS1105, SIS1106, SIS 4010 and SIS 4019.

[0015] Furthermore, the first rubber is natural rubber, preferably the natural rubber is cis-1,4-polyisoprene, more preferably the weight average molecular weight of cis-1,4-polyisoprene is 400,000 to 3,000,000, and the weight percentage of the cis structure is ≥97wt%.

[0016] Furthermore, the glass transition temperature of the nitrile rubber is ≤-50°C, more preferably -60 to -55°C; preferably, the weight percentage of acrylonitrile monomer in the nitrile rubber is 20 to 50wt%; preferably, the Mooney viscosity of the nitrile rubber at 100°C is 50 to 75.

[0017] Furthermore, the rare earth butadiene rubber is a neodymium-based rare earth butadiene rubber, and preferably the neodymium-based rare earth butadiene rubber has a weight average molecular weight of 800,000 to 900,000, a number average molecular weight of 200,000 to 300,000, and a relative molecular mass distribution of 3.0 to 4.5.

[0018] Furthermore, the aspect ratio of the nano-silica rods is (50-500):(1-50), and more preferably the diameter is 5-25 nm and the length is 80-100 nm.

[0019] Further, the silane coupling agent is selected from one or more of thiocarboxyl silane, vinyl silane, epoxy silane and methacryloxy silane; preferably, the silane coupling agent is selected from one or more of 3-(octanoylthio)propyltriethoxysilane, 3-propionylthio-1-propyltriethoxysilane, vinyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane.

[0020] Furthermore, the self-sealing adhesive composition further comprises: a filler, a plasticizer, an antioxidant, an activator and a tackifying resin; preferably, in parts by weight, the self-sealing adhesive composition further comprises: 5 to 20 parts of filler, 20 to 60 parts of plasticizer, 1 to 5 parts of antioxidant, 2 to 8 parts of activator and 5 to 50 parts of tackifying resin; preferably, in parts by weight, the self-sealing adhesive composition further comprises: 10 to 15 parts of filler, 30 to 40 parts of plasticizer, 2 to 3 parts of antioxidant, 2 to 5 parts of activator and 10 to 30 parts of tackifying resin.

[0021] Furthermore, the filler is selected from one or more of white carbon black, graphene, hollow glass microspheres and clay, and preferably the filler is a combination of rice husk-derived white carbon black, graphene and hollow glass microspheres; more preferably, the pH value of the rice husk-derived white carbon black is 5 to 7, and the nitrogen adsorption specific surface area is 150 to 175 m 2 / g, the adsorption specific surface area of ​​hexadecyltrimethylammonium bromide is 130~165m 2 / g; more preferably, the mesh number of graphene is 50-600 mesh, and the thermal conductivity is 600-3500W / mK; more preferably, the material of the hollow glass microspheres is borosilicate, and the average particle size is 10-250μm, and the wall thickness is 1-2μm.

[0022] Furthermore, the plasticizer is selected from one or more of paraffin, paraffin oil, coal tar, coumarone resin, environmentally friendly aromatic oil, and cycloalkane oil. Preferably, the plasticizer is paraffin oil, and more preferably, the density of paraffin oil at 20°C is 0.75-0.95g / mL and the flash point is 120-200°C.

[0023] Furthermore, the antioxidant is selected from one or more of tert-butylhydroxybenzoate, p-hydroxybenzoate and tri-tert-butylhydroxybenzoate.

[0024] Furthermore, the activator is selected from inorganic activators and / or organic activators, preferably the inorganic activator is selected from one or more of zinc oxide, calcium oxide, magnesium oxide and lead oxide, and preferably the organic activator is selected from one or more of stearic acid, octanoic acid, zinc stearate and ethanolamine.

[0025] Furthermore, the tackifying resin is selected from gum rosin and / or xylene resin.

[0026] Furthermore, the self-sealing adhesive composition further comprises: a vulcanizing agent and a vulcanization accelerator; preferably, by weight, the self-sealing adhesive composition further comprises: 0.01 to 10 parts of a vulcanizing agent and 0.01 to 10 parts of a vulcanization accelerator, preferably 0.1 to 0.3 parts of a vulcanizing agent and 0.1 to 0.2 parts of a vulcanization accelerator; preferably, the vulcanizing agent is sulfur; preferably, the vulcanization accelerator is selected from thiuram vulcanization accelerators and / or guanidine vulcanization accelerators; more preferably, the thiuram vulcanization accelerator is selected from tetramethylthiuram monosulfide, One or more of tetraisobutylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabenzylthiuram disulfide, methylphenylthiuram disulfide and bis(1,5-pentylene)thiuram tetrasulfide; more preferably, the guanidine vulcanization accelerator is selected from one or more of diphenylguanidine, di-o-tolylguanidine and o-tolylbiguanide; more preferably, the vulcanization accelerator is a combination of a thiuram vulcanization accelerator and a guanidine vulcanization accelerator, and the weight ratio of the two is (0.5-1.5):(0.1-1).

[0027] The second aspect of the present application also provides a self-sealing rubber material, which is prepared by mixing and vulcanizing the above-mentioned self-sealing rubber material composition provided by the present application.

[0028] The third aspect of the present application also provides a method for preparing the above-mentioned self-sealing rubber material provided by the present application, and the preparation method comprises: step S1, mixing the first rubber, the second rubber, the thermoplastic elastomer, the nano-silica rods, the silane coupling agent and the compatibilizer to obtain a first masterbatch; step S2, mixing the third rubber with a vulcanizing agent to obtain a second masterbatch; step S3, co-extruding the first masterbatch and the second masterbatch to obtain a mixed rubber material; step S4, vulcanizing the mixed rubber material to obtain a self-sealing rubber material.

[0029] Furthermore, in step S1, the temperature of banburying is 60-80° C. and the time is 5-9 min; preferably, stirring is performed during the banburying process, and more preferably the stirring rate is 60-100 rpm.

[0030] Furthermore, in step S4, the vulcanization temperature is 100-180° C., the pressure is 5-10 MPa, and the time is 3-20 min.

[0031] Furthermore, fillers and plasticizers are added in step S1.

[0032] Furthermore, in step S2, the mixing temperature is 40-60°C and the mixing time is 3-5 min; preferably, stirring is performed during the mixing process, and more preferably the stirring rate is 40-100 rpm; preferably, an activator, an antioxidant and a vulcanization accelerator are also added in step S2.

[0033] Furthermore, a tackifier is added in step S3.

[0034] The fourth aspect of the present application also provides the self-sealing rubber composition provided by the present application, or the use of the self-sealing rubber provided by the present application in the field of tires.

[0035] Using the technical solution of the present invention, the compatibilizer in the present application is a modified ethylene-ethyl acrylate copolymer, the structure of which includes a chain segment corresponding to the second styrene-isoprene-styrene block copolymer and a grafted group corresponding to maleic anhydride. Compared with other types, the use of a specific type of compatibilizer in the present application can improve the compatibility of the components in the self-sealing rubber composition, better exert the synergistic effect of the components, and improve the processability of the self-sealing rubber composition; the compatibilizer having a specific structure of the present application is introduced into the self-sealing rubber composition. On the one hand, by grafting styrene-isoprene-styrene chain segments into the ethylene-ethyl acrylate copolymer, an organic fusion with the thermoplastic elastomer styrene-isoprene-styrene block copolymer (SIS) in the self-sealing rubber composition can be achieved. On the second hand, polar segments such as ester groups exist in the ethylene-ethyl acrylate copolymer, which can generate intermolecular forces with polar segments such as cyano groups present in nitrile rubber, thereby achieving interfacial fusion with nitrile rubber. On the third hand, groups such as hydroxyl groups and phenolic hydroxyl groups in the compatibilizer can undergo interfacial chemical bonding with silane coupling agents. The combination of the above three aspects can realize the construction of a physical cross-linked network structure in the self-sealing rubber composition, thereby improving the structural stability and air tightness of the self-sealing rubber obtained; at the same time, the compounding of the first rubber, the second rubber, the third rubber and the thermoplastic elastomer of a specific type in the self-sealing rubber composition of the present application can improve the high and low temperature resistance of the self-sealing rubber. The nano silica rod itself has excellent mechanical strength and high temperature resistance. At the same time, the silanol groups on the surface of the nano silica rod and the silane coupling agent can undergo an interfacial chemical reaction, thereby ensuring that it has good compatibility with each component in the self-sealing rubber composition. The introduction of the nano silica rod into the self-sealing rubber composition can play its reinforcing role, and can improve the stability of the self-sealing rubber obtained therefrom under high temperature and high pressure environments in tires, and inhibit the self-sealing rubber from flowing at high temperatures or when the tire rotates at high speeds, thereby improving the driving safety of the car.

[0036] Compared with the prior art, the self-sealing rubber composition provided by the present application has better high and low temperature resistance and processability, and the self-sealing rubber composition provided by the present application has a structurally stable physical cross-linked network structure, so that a stable cross-linked network structure can be obtained without introducing a vulcanizer, or only with the use of a small amount of vulcanizer and vulcanization accelerator, which is beneficial to reduce the amount of vulcanizer and vulcanization accelerator, and thus can reduce the pollution of the vulcanizer and vulcanization accelerator to the environment; the self-sealing rubber prepared from the above-mentioned self-sealing rubber composition of the present application has good structural stability and air tightness, and is not easy to flow inside the tire due to local heat accumulation; when the self-sealing rubber prepared from the rubber composition provided by the present application is used as a self-sealing agent in a tire, after the tire is punctured by a foreign object, it can quickly wrap the punctured part to inhibit tire leakage, and when the foreign object is pulled out, the self-sealing rubber can quickly flow to block the puncture under the action of the air pressure in the tire, inhibiting the occurrence of slow tire leakage or tire blowout. DETAILED DESCRIPTION

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0038] As described in the background technology, the existing self-sealing rubber of the self-sealing tire has the problems of difficult mixing and processing, the presence of environmentally polluting components in the formula, poor high and low temperature resistance of the self-sealing rubber, and easy flow at high temperatures, which causes hidden dangers to driving safety. In order to solve the above technical problems, the first aspect of the present application provides a self-sealing rubber composition, which includes: a first rubber, a second rubber, a third rubber, a thermoplastic elastomer, a nano-silica rod, a silane coupling agent and a compatibilizer; wherein the first rubber is selected from natural rubber and / or polyisoprene rubber, the second rubber is nitrile rubber, and the third rubber is rare earth butadiene rubber; the compatibilizer is a modified ethylene-ethyl acrylate copolymer, which is obtained by reacting a first styrene-isoprene-styrene block copolymer and maleic anhydride with an ethylene-ethyl acrylate copolymer under the action of an initiator; the thermoplastic elastomer is a second styrene-isoprene-styrene block copolymer (SIS).

[0039] The compatibilizer in the present application is a modified ethylene-ethyl acrylate copolymer, and its structure includes a first styrene-isoprene-styrene block copolymer corresponding segment and a maleic anhydride corresponding grafted group. Compared with other types, the use of a specific type of compatibilizer in the present application can improve the compatibility of each component in the self-sealing adhesive composition, better play the synergistic effect of each component, and improve the processability of the self-sealing adhesive composition. The compatibilizer with a specific structure of the present application is introduced into the self-sealing adhesive composition. On the one hand, by grafting styrene-isoprene-styrene segments in ethylene-ethyl acrylate copolymers, it is possible to achieve organic fusion with the thermoplastic elastomer (second styrene-isoprene-styrene block copolymer, SIS) in the self-sealing adhesive composition; on the second hand, there are polar segments such as ester groups in ethylene-ethyl acrylate copolymers, which can have intermolecular forces with polar segments such as cyano groups present in nitrile rubber, thereby achieving interfacial fusion with nitrile rubber; on the third hand, groups such as hydroxyl groups and phenolic hydroxyl groups in the compatibilizer can undergo interfacial chemical bonding with silane coupling agents. The combination of the above three aspects can realize the construction of a physical cross-linked network structure in the self-sealing rubber composition, thereby improving the structural stability and air tightness of the self-sealing rubber obtained; at the same time, the compounding of the first rubber, the second rubber, the third rubber and the thermoplastic elastomer of a specific type in the self-sealing rubber composition of the present application can improve the high and low temperature resistance of the self-sealing rubber. The nano silica rod itself has excellent mechanical strength and high temperature resistance. At the same time, the silanol groups on the surface of the nano silica rod and the silane coupling agent can undergo an interfacial chemical reaction, thereby ensuring that it has good compatibility with each component in the self-sealing rubber composition. The introduction of the nano silica rod into the self-sealing rubber composition can play its reinforcing role, and can improve the stability of the self-sealing rubber obtained therefrom under high temperature and high pressure environments in tires, and inhibit the self-sealing rubber from flowing at high temperatures or when the tire rotates at high speeds, thereby improving the driving safety of the car.

[0040] The self-sealing rubber composition provided by the present application has better high and low temperature resistance and processability, and there is a structurally stable physical cross-linked network structure in the self-sealing rubber composition provided by the present application, so that under the premise of not introducing a vulcanizing agent, or only a small amount of vulcanizing agent and vulcanization accelerator are needed to obtain a stable cross-linked network structure, which is conducive to reducing the amount of vulcanizing agent and vulcanization accelerator, and then can reduce the pollution of the environment by the vulcanizing agent and vulcanization accelerator. The self-sealing rubber prepared by the above-mentioned self-sealing rubber composition of the present application has good structural stability and airtightness, and is not easy to flow inside the tire due to local heat accumulation; when the self-sealing rubber prepared by the rubber composition provided by the present application is used as a self-sealing agent in a tire, after the tire is punctured by a foreign body, the puncture site can be quickly wrapped to suppress tire leakage, and when the foreign body is pulled out, the self-sealing rubber can flow rapidly under the action of the air pressure in the tire to block the puncture, suppressing the occurrence of slow tire leakage or blowout.

[0041] In a preferred embodiment, the self-sealing rubber composition comprises, by weight: 20 to 50 parts of the first rubber, 20 to 50 parts of the second rubber, 20 to 50 parts of the third rubber, 10 to 30 parts of the thermoplastic elastomer, 5 to 20 parts of nano-silica rods, 1 to 10 parts of silane coupling agents and 5 to 15 parts of compatibilizers. The weight percentages of each component in the self-sealing rubber composition include but are not limited to the above ranges, and limiting it within the above ranges is conducive to improving the compatibility of each component, and is conducive to better exerting the synergistic effect of each component, thereby helping to improve its processability, and also helping to improve the utilization rate of each component.

[0042] In order to further improve the compatibility of the components in the self-sealing rubber composition, further exert the synergistic effect of the components, further improve its processability, and also to further improve the utilization rate of the components, preferably, the self-sealing rubber composition includes, by weight: 30 to 50 parts of the first rubber, 20 to 30 parts of the second rubber, 20 to 30 parts of the third rubber, 10 to 20 parts of the thermoplastic elastomer, 15 to 20 parts of nano silica rods, 1 to 5 parts of silane coupling agents and 5 to 10 parts of compatibilizers.

[0043] In a preferred embodiment, the ethylene-ethyl acrylate copolymer has a structure shown in formula (I):

[0044]

[0045] Among them, R 1 Including but not limited to vinylene, propenylene or C 2 ~C 6 A straight chain alkylene group; R 2 Including but not limited to C 2 ~C 5x is any integer between 10 and 30, and y is any integer between 10 and 30.

[0046] Compared with other types, the use of ethylene-ethyl acrylate copolymer having a structure shown in formula (I) is conducive to improving the compatibility of the components in the self-sealing rubber composition, and is conducive to forming a more stable physical cross-linked network structure after mixing, thereby improving the processability of the self-sealing rubber composition, and is conducive to improving the structural stability and air tightness of the prepared self-sealing rubber. Moreover, compared with other ranges, limiting x and y in formula (I) to the above ranges is conducive to improving the structural stability of the ethylene-ethyl acrylate copolymer, and is conducive to its role as a compatibilizer after modification, thereby facilitating the formation of a more stable physical cross-linked network structure after mixing.

[0047] In a preferred embodiment, the corresponding segment of the first styrene-isoprene-styrene block copolymer in the compatibilizer includes a first styrene repeating unit and a first isoprene repeating unit, and preferably the weight ratio of the first styrene repeating unit to the first isoprene repeating unit is (10-50):(50-90), and the weight average molecular weight of the corresponding segment of the first styrene-isoprene-styrene block copolymer in the compatibilizer is 25,000 to 28,000.

[0048] Compared with other structures, grafting a chain segment with the above structure is beneficial to improving the compatibility of the compatibilizer, thereby improving the compatibility of the components in the self-sealing rubber composition, better exerting the synergistic effect of the components, improving the processability of the self-sealing rubber composition, and forming a structurally stable physical cross-linked network structure, thereby improving the structural stability and air tightness of the self-sealing rubber and improving its self-sealing performance.

[0049] In a preferred embodiment, in the compatibilizer, the grafting rate of the corresponding segment of the first styrene-isoprene-styrene block copolymer is 40-60wt%, and the grafting rate of the corresponding grafting group of maleic anhydride is 40-60wt%. Compared with other ranges, limiting the grafting rate of the above-mentioned segment and the above-mentioned grafting group in the compatibilizer to the above-mentioned range is conducive to improving the compatibility of the compatibilizer, thereby improving the compatibility of each component, thereby better exerting the synergistic effect of each component, and improving the processability of the self-sealing rubber composition, and forming a structurally stable physical cross-linked network structure, thereby improving the structural stability and air tightness of the self-sealing rubber, and improving its self-sealing performance.

[0050] In order to regulate the grafting rate of the corresponding segment of the first styrene-isoprene-styrene block copolymer and the corresponding grafting group of maleic anhydride within a more suitable range, thereby further improving the compatibility of the prepared compatibilizer, preferably, the weight ratio of ethylene-ethyl acrylate copolymer, the first styrene-isoprene-styrene block copolymer, maleic anhydride and initiator is (95-120):(32-62):(1-9):(3-13).

[0051] In a preferred embodiment, the second styrene-isoprene-styrene block copolymer in the thermoplastic elastomer includes a second styrene repeating unit and a second isoprene repeating unit, and the weight ratio of the second styrene repeating unit to the second isoprene repeating unit is (10-40): (60-90). The weight ratio of the above repeating units in the thermoplastic elastomer includes but is not limited to the above range, and limiting it within the above range is conducive to improving the viscosity and processability of the thermoplastic elastomer, thereby improving the processability of the self-sealing rubber composition, and at the same time, it is also conducive to improving the high and low temperature resistance of the thermoplastic elastomer, thereby improving the high and low temperature resistance of the prepared self-sealing rubber.

[0052] In order to further improve the processability and high and low temperature resistance of the thermoplastic elastomer, thereby further improving the processability of the self-sealing rubber composition and further improving the high and low temperature resistance of the prepared self-sealing rubber, preferably, the average molecular weight of the thermoplastic elastomer is 80,000 to 120,000.

[0053] Oil-filled thermoplastic elastomer refers to adding a certain amount of filler oil to the basic thermoplastic elastomer material to improve the processing performance of the thermoplastic elastomer and increase its fluidity. In a preferred embodiment, the thermoplastic elastomer includes but is not limited to one or more of SIS1105, SIS1106, SIS 4010 and SIS 4019. Compared with other types, the use of the above-mentioned types of thermoplastic elastomer is conducive to improving the fluidity and flexibility of the thermoplastic elastomer, and is conducive to improving its processing performance, thereby helping to improve the processability of the self-sealing rubber composition.

[0054] In order to improve the compatibility of the extending oil with the thermoplastic elastomer, thereby further improving the processing performance of the thermoplastic elastomer and further improving the processability of the self-sealing rubber composition, preferably, the extending oil includes but is not limited to cyclohexane oil and / or paraffin oil.

[0055] Cis-1,4-polyisoprene itself has excellent wear resistance, aging resistance, low temperature resistance and environmental adaptability. In a preferred embodiment, the first rubber is natural rubber, preferably the natural rubber is cis-1,4-polyisoprene. Compared with other types, the use of the first rubber of the above type is conducive to improving the compatibility of the first rubber with other components in the self-sealing rubber composition, and is conducive to improving its processability, and is also conducive to improving the viscoelasticity and low temperature resistance of the prepared self-sealing rubber, thereby helping to improve the self-sealing performance of the self-sealing rubber and broaden its use temperature.

[0056] In order to further improve the compatibility of the first rubber with other components in the self-sealing rubber composition, further improve the viscoelasticity and low temperature resistance of the first rubber, thereby further improving the viscoelasticity and low temperature resistance of the prepared self-sealing rubber, preferably, the weight average molecular weight of cis-1,4-polyisoprene is 400,000 to 3,000,000, and the weight percentage of its cis structure is ≥97wt%.

[0057] In a preferred embodiment, the glass transition temperature of the nitrile rubber is ≤-50° C., preferably -60 to -55° C. The glass transition temperature (Tg) of the nitrile rubber includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the viscoelasticity and low temperature resistance of the nitrile rubber, and is beneficial to improving the fluidity of the nitrile rubber, improving its processing performance, thereby being beneficial to improving the processability of the self-sealing rubber composition and the low temperature resistance and self-sealing performance of the prepared self-sealing rubber.

[0058] In a preferred embodiment, the weight percentage of acrylonitrile monomer in the nitrile rubber is 20-50wt%. The weight percentage of acrylonitrile monomer in the nitrile rubber includes but is not limited to the above range, and limiting it within the above range is conducive to introducing an appropriate amount of polar segments containing cyano groups into the nitrile rubber, and is conducive to enhancing the intermolecular force between the polar segments and the polar segments containing ester groups in the compatibilizer, thereby helping to improve the compatibility of the nitrile rubber with other components in the self-sealing rubber composition, and is also conducive to improving the wear resistance, high and low temperature resistance and air tightness of the nitrile rubber, thereby helping to improve the wear resistance, high and low temperature resistance and air tightness of the self-sealing rubber.

[0059] In order to further improve the processability of nitrile rubber, thereby further improving the wear resistance, high and low temperature resistance and air tightness of the self-sealing rubber, preferably, the Mooney viscosity (ML1+4) of the nitrile rubber at 100°C is 50-75.

[0060] Neodymium rare earth butadiene rubber has excellent tensile strength, anti-flexing performance, wear resistance and processing performance. In a preferred embodiment, the rare earth butadiene rubber is neodymium rare earth butadiene rubber, preferably the weight average molecular weight of neodymium rare earth butadiene rubber is 800,000 to 900,000, the number average molecular weight is 200,000 to 300,000, and the relative molecular mass distribution is 3.0 to 4.5. The weight average molecular weight, number average molecular weight and relative molecular mass distribution of neodymium rare earth butadiene rubber include but are not limited to the above ranges, and limiting it within the above ranges is conducive to improving the processability of the self-sealing rubber composition, and is conducive to improving the structural stability and wear resistance of the self-sealing rubber.

[0061] In a preferred embodiment, the aspect ratio of the nano-silica rods is (50-500): (1-50). The aspect ratio of the nano-silica rods includes but is not limited to the above range. Limiting it within the above range is conducive to better exerting its reinforcing effect, and is conducive to improving the stability of the self-sealing rubber composition under high temperature and high pressure environment in the tire, and is conducive to inhibiting the self-sealing rubber from flowing at high temperature or when the tire rotates at high speed, thereby improving the driving safety of the car.

[0062] In order to further improve the stability of the self-sealing rubber composition under high temperature and high pressure environment in the tire, and further inhibit the flow of the self-sealing rubber under high temperature or high speed rotation of the tire, preferably, the diameter of the nano-silica rod is 5-25nm and the length is 80-100nm.

[0063] In a preferred embodiment, the silane coupling agent includes but is not limited to one or more of thiocarboxyl silane, vinyl silane, epoxy silane and methacryloxy silane. Compared with other types, the use of the above-mentioned types of silane coupling agents is conducive to improving the interface between the nano-silica rods and other components and the first rubber, the second rubber and the third rubber, thereby facilitating the improvement of the compatibility and dispersibility of the components in the self-sealing rubber composition, and improving the structural stability of the self-sealing rubber obtained.

[0064] In order to further improve the interfacial effect between the nano-silica rods and other components and the first rubber, the second rubber and the third rubber, thereby further improving the compatibility and dispersibility of the components in the self-sealing rubber composition, preferably, the silane coupling agent includes but is not limited to one or more of 3-(octanoylthio)propyltriethoxysilane (NXT), 3-propionylthio-1-propyltriethoxysilane (PXT), vinyltrimethoxysilane (VTMS) and 3-(methacryloyloxy)propyltrimethoxysilane (KH-570).

[0065] The introduction of fillers is conducive to improving the mechanical strength, air tightness and high and low temperature resistance of the self-sealing rubber compound; the introduction of plasticizers is conducive to improving the processing performance of the self-sealing rubber compound composition; the introduction of antioxidants is conducive to improving the aging resistance of the self-sealing rubber compound; the introduction of activators is conducive to improving the processability and thermal stability of the self-sealing rubber compound composition, and is conducive to improving its crosslinking efficiency and vulcanization speed; the introduction of tackifying resins is conducive to improving the adhesion of the self-sealing rubber compound, and is conducive to improving its adhesion to the inner wall of the tire, thereby helping to improve its self-sealing performance. In a preferred embodiment, the self-sealing rubber compound composition also includes: fillers, plasticizers, antioxidants, activators and tackifying resins.

[0066] In a preferred embodiment, the self-sealing adhesive composition further comprises, by weight: 5 to 20 parts of filler, 20 to 60 parts of plasticizer, 1 to 5 parts of antioxidant, 2 to 8 parts of activator and 5 to 50 parts of tackifying resin. The weight parts of filler, plasticizer, antioxidant, activator and tackifying resin include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the processability of the self-sealing adhesive composition, and is conducive to improving the mechanical strength, air tightness, high and low temperature resistance, aging resistance and adhesion of the prepared self-sealing adhesive, and is also conducive to improving the utilization rate of each component.

[0067] In order to further improve the processability of the self-sealing adhesive composition, further improve the comprehensive properties of the prepared self-sealing adhesive such as mechanical strength, air tightness, high and low temperature resistance, aging resistance and adhesion, and at the same time to further improve the utilization rate of each component, preferably, the self-sealing adhesive composition also includes, by weight: 10 to 15 parts of filler, 30 to 40 parts of plasticizer, 2 to 3 parts of antioxidant, 2 to 5 parts of activator and 10 to 30 parts of tackifying resin.

[0068] Rice husk source white carbon black is extracted from rice husk, a byproduct of rice processing. Its main components are hydrated silicon dioxide and hydrocarbons. It is an ideal raw material for producing white carbon black, and its rice husk waste can be recycled; the layered structure of graphene is conducive to improving the air tightness of the self-sealing rubber compound, and its tightly stacked single-layer two-dimensional lattice structure can extend the distance and time of gas permeation in the rubber-filler network, thereby helping to block gas penetration. At the same time, graphene also has good compatibility in the rubber matrix; hollow glass microspheres have a reinforcing effect, which is conducive to inhibiting the flow of self-sealing rubber compounds at high temperatures or high-speed rotation of tires. At the same time, the density of hollow glass microspheres is relatively small, which is conducive to reducing the weight of the composition, thereby facilitating the development of lightweight tires. In a preferred embodiment, the filler includes but is not limited to one or more of white carbon black, graphene, hollow glass microspheres and clay. Compared with other types, the use of the above-mentioned types of fillers is conducive to improving the mechanical strength, air tightness and high and low temperature resistance of the self-sealing rubber compound, thereby helping to improve its self-sealing performance. Preferably, the filler is a combination of rice husk-derived white carbon black, graphene and hollow glass microspheres.

[0069] In order to further improve the mechanical strength, air tightness and high and low temperature resistance of the prepared self-sealing rubber material, thereby further improving the self-sealing performance of the self-sealing rubber material, preferably, the pH value of the rice husk source white carbon black is 5-7, and the nitrogen adsorption specific surface area is 150-175m 2 / g, hexadecyltrimethylammonium bromide (CTAB) adsorption specific surface area is 130~165m 2 / g; the mesh number of graphene is 50-600 mesh, and the thermal conductivity is 600-3500W / mK; the material of the hollow glass microspheres is borosilicate, and its average particle size is 10-250μm, and the wall thickness is 1-2μm.

[0070] In a preferred embodiment, the plasticizer includes, but is not limited to, one or more of paraffin, paraffin oil, coal tar, coumarone resin, environmentally friendly aromatic oil (TDAE), and naphthenic oil. Compared with other types, the use of the above-mentioned types of plasticizers is conducive to improving the processing properties of the self-sealing rubber compound and improving the viscosity and elasticity of the prepared self-sealing rubber compound.

[0071] In order to further improve the processing properties of the self-sealing rubber compound and further improve the viscosity and elasticity of the prepared self-sealing rubber compound, preferably, the plasticizer is paraffin oil, and more preferably, the density of the paraffin oil at 20°C is 0.75-0.95 g / mL and the flash point is 120-200°C.

[0072] In a preferred embodiment, the antioxidant includes but is not limited to one or more of tert-butylhydroxybenzoate (BHT), parahydroxybenzoate (BHA) and tri-tert-butylhydroxybenzoate (TBHQ). Compared with other types, the use of the above types of antioxidants is conducive to improving the aging resistance of the self-sealing rubber compound.

[0073] Inorganic activators have the characteristics of good thermal stability, low cost and wide application range; organic activators can improve processing performance, and can also improve crosslinking efficiency and vulcanization rate. In a preferred embodiment, the activator includes but is not limited to inorganic activators and / or organic activators, the inorganic activator includes but is not limited to one or more of zinc oxide, calcium oxide, magnesium oxide and lead oxide, and the organic activator includes but is not limited to one or more of stearic acid, octanoic acid, zinc stearate and ethanolamine. Compared with other types, the use of the above-mentioned types of activators is conducive to improving the processability of the self-sealing adhesive composition, the efficiency of subsequent vulcanization, and the thermal stability of the prepared self-sealing adhesive.

[0074] In a preferred embodiment, the tackifying resin includes but is not limited to gum rosin and / or xylene resin. Compared with other types, the use of the above-mentioned tackifying resin is conducive to improving the adhesion of the self-sealing rubber compound, and is conducive to improving its adhesion to the inner wall of the tire, thereby helping to improve the self-sealing performance of the self-sealing rubber compound.

[0075] The vulcanizing agent can promote the cross-linking between rubber molecules, which is conducive to forming a three-dimensional network structure; the vulcanization accelerator can increase the vulcanization reaction rate, which is conducive to reducing the vulcanization temperature, reducing energy consumption, and also helping to improve the uniformity of vulcanization. In a preferred embodiment, the self-sealing rubber composition also includes: a vulcanizing agent and a vulcanization accelerator.

[0076] In a preferred embodiment, the self-sealing rubber composition further comprises, by weight: 0.01 to 10 parts of a vulcanizing agent and 0.01 to 10 parts of a vulcanization accelerator. The weight parts of the vulcanizing agent and the vulcanization accelerator include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the vulcanization efficiency, and is conducive to improving the structural stability of the self-sealing rubber obtained by vulcanization, thereby helping to improve its self-sealing performance.

[0077] In order to further improve the vulcanization efficiency, further improve the structural stability of the self-sealing rubber obtained by vulcanization, and thus further improve its self-sealing performance, preferably, the self-sealing rubber composition further includes, by weight: 0.1 to 0.3 parts of a vulcanizing agent and 0.1 to 0.2 parts of a vulcanization accelerator.

[0078] The vulcanizing agent used in the present application can be any commonly used type in the art. In a preferred embodiment, the vulcanizing agent is sulfur.

[0079] In a preferred embodiment, the vulcanization accelerator includes but is not limited to thiuram vulcanization accelerator and / or guanidine vulcanization accelerator. Compared with other types, the use of the above types of vulcanization accelerators is beneficial to improving the vulcanization reaction rate, improving the uniformity of vulcanization, and improving the storage stability of the mixed rubber.

[0080] In order to further improve the vulcanization reaction rate, further improve the uniformity of vulcanization, and further improve the storage stability of the mixed rubber, preferably, the thiuram vulcanization accelerator includes but is not limited to one or more of tetramethylthiuram monosulfide (TMTM), tetraisobutylthiuram monosulfide (TiBTM), tetramethylthiuram disulfide (TMTD), tetraethylthiuram disulfide (TETD), tetrabenzylthiuram disulfide (TBzTD), methylphenylthiuram disulfide (MPhTD) and bis(1,5-pentylene)thiuram tetrasulfide (DPTT); the guanidine vulcanization accelerator includes but is not limited to one or more of diphenylguanidine (DPG), di-o-tolylguanidine (DOTG) and o-tolylbiguanide (OTBG).

[0081] In order to further improve the vulcanization reaction rate, further improve the uniformity of vulcanization, and to further improve the storage stability of the mixed rubber, preferably, the vulcanization accelerator is a combination of a thiuram vulcanization accelerator and a guanidine vulcanization accelerator, and the weight ratio of the two is (0.5-1.5):(0.1-1).

[0082] The second aspect of the present application also provides a self-sealing rubber material, which is prepared by mixing and vulcanizing the above-mentioned self-sealing rubber material composition provided by the present application.

[0083] The self-sealing rubber composition provided by the present application has better high and low temperature resistance and processability, and there is a structurally stable physical cross-linked network structure in the self-sealing rubber composition provided by the present application, so that only a small amount of vulcanizer and vulcanization accelerator is needed to obtain a stable cross-linked network structure, which is beneficial to reduce the amount of vulcanizer and vulcanization accelerator, and thus can reduce the pollution of the vulcanizer and vulcanization accelerator to the environment; the self-sealing rubber prepared from the self-sealing rubber composition of the present application has good structural stability and air tightness, and is not easy to flow inside the tire due to local heat accumulation; when the self-sealing rubber provided by the present application is used as a self-sealing agent in a tire, after the tire is punctured by a foreign object, it can quickly wrap the punctured part to inhibit tire leakage, and when the foreign object is pulled out, the self-sealing rubber can quickly flow under the action of the air pressure in the tire to block the puncture, thereby inhibiting the occurrence of slow tire leakage or tire blowout.

[0084] The third aspect of the present application also provides a method for preparing a self-sealing rubber compound, which comprises: step S1, mixing a first rubber, a second rubber, a thermoplastic elastomer, a nano-silica rod, a silane coupling agent and a compatibilizer to obtain a first masterbatch; step S2, mixing the third rubber with a vulcanizing agent to obtain a second masterbatch; step S3, co-extruding the first masterbatch and the second masterbatch to obtain a mixed rubber compound; step S4, vulcanizing the mixed rubber compound to obtain a self-sealing rubber compound.

[0085] The first masterbatch can be obtained through step S1, and the dispersibility of each component in step S1 can be improved. Step S2 can improve the dispersibility of the third rubber and the vulcanizing agent, thereby improving the subsequent vulcanization efficiency; step S3 can improve the dispersibility of each component, thereby improving the mixing efficiency and the subsequent vulcanization efficiency; step S4 vulcanizes the mixed rubber material to improve the structural stability of the obtained self-sealing rubber material, thereby improving the physical properties and mechanical properties of the obtained self-sealing rubber material, such as mechanical strength, creep resistance and high temperature resistance.

[0086] Mixing and vulcanizing the above-mentioned materials can obtain a self-sealing rubber compound. The above-mentioned self-sealing rubber compound composition provided by the present application has better high and low temperature resistance and processability, and there is a structurally stable physical cross-linked network structure in the self-sealing rubber compound composition provided by the present application, so that only a small amount of vulcanizing agent and vulcanization accelerator are needed to obtain a stable cross-linked network structure, which is conducive to reducing the amount of vulcanizing agent and vulcanization accelerator, and then the pollution of the environment by the vulcanizing agent and vulcanization accelerator can be reduced. The self-sealing rubber compound prepared by the above-mentioned self-sealing rubber compound composition of the present application has good structural stability and air tightness, and is not easy to flow inside the tire due to local heat accumulation. When the above-mentioned self-sealing rubber compound provided by the present application is applied to the tire as a self-sealing agent, after the tire is punctured by a foreign body, the puncture site can be quickly wrapped to suppress tire leakage, and when the foreign body is pulled out, the self-sealing rubber compound can flow rapidly under the action of the air pressure in the tire to block the puncture port, suppressing the occurrence of slow tire leakage or blowout.

[0087] In a preferred embodiment, in step S1, the banburying temperature is 60-80°C and the time is 5-9 minutes. The banburying temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersibility of each component, improving the efficiency of banburying, and facilitating subsequent molding and vulcanization processes.

[0088] In order to further improve the dispersion uniformity of each component and further improve the efficiency of banburying, preferably, stirring is performed during the banburying process, and more preferably the stirring rate is 60-100 rpm.

[0089] In a preferred embodiment, in step S4, the vulcanization temperature is 100-180°C, the pressure is 5-10 MPa, and the time is 3-20 min. The vulcanization temperature, pressure and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the efficiency of vulcanization and the mechanical properties of the prepared self-sealing rubber compound.

[0090] In order to improve the mechanical strength, air tightness, high and low temperature resistance and aging resistance of the prepared self-sealing adhesive, preferably, fillers and plasticizers are also added in step S1.

[0091] In a preferred embodiment, in step S2, the mixing temperature is 40-60° C. and the mixing time is 3-5 min. The mixing temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersibility of the third rubber and the vulcanizing agent, thereby facilitating improving the efficiency of subsequent vulcanization.

[0092] In order to further improve the dispersibility of the third rubber and the vulcanizing agent, and thus further improve the efficiency of subsequent vulcanization, preferably, stirring is performed during the mixing process, and more preferably, the stirring rate is 40 to 100 rpm.

[0093] In order to improve the processability of the self-sealing rubber composition, improve the aging resistance of the self-sealing rubber, and further improve the vulcanization efficiency, preferably, an activator, an antioxidant and a vulcanization accelerator are also added in step S2.

[0094] In order to improve the cohesiveness of the prepared self-sealing rubber material, improve its adhesion to the inner wall of the tire, and at the same time to improve the self-sealing performance of the self-sealing rubber material, preferably, a tackifier is also added in step S3.

[0095] The fourth aspect of the present application also provides the self-sealing rubber composition provided by the present application, or the use of the self-sealing rubber provided by the present application in the field of tires.

[0096] The above-mentioned self-sealing rubber composition provided by the present application has better high and low temperature resistance and processability, and there is a structurally stable physical cross-linked network structure in the self-sealing rubber composition provided by the present application, so that under the premise of not introducing a vulcanizing agent, or only a small amount of vulcanizing agent and vulcanization accelerator need to be used to obtain a stable cross-linked network structure, which is conducive to reducing the amount of vulcanizing agent and vulcanization accelerator, and then the pollution of vulcanizing agent and vulcanization accelerator to the environment can be reduced. The self-sealing rubber obtained by the above-mentioned self-sealing rubber composition of the present application has good structural stability and airtightness, and is not easy to flow inside the tire due to local heat accumulation. When the self-sealing rubber obtained by the rubber composition provided by the present application is applied in the tire as a self-sealing agent, after the tire is pierced by a foreign body, the puncture site can be quickly wrapped to suppress tire leakage, and when the foreign body is pulled out, the self-sealing rubber can flow rapidly under the action of the air pressure in the tire to block the puncture, suppressing the occurrence of slow leakage or blowout of the tire.

[0097] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0098] It should be noted that the types and amounts of the components in Examples 1 to 9 are shown in Tables 1 and 2. The preparation method of the compatibilizer used in Examples 1 to 19 is as follows: ethylene-ethyl acrylate copolymer (SK Group of South Korea, EEA6200), SIS (Sinopec Baling Petrochemical, 4010), maleic anhydride and dibenzoyl peroxide initiator in a weight ratio of 100:40:5:6 are mixed with 500 mL of n-hexane, and reacted in a closed container at 100° C. for 10 hours to obtain a compatibilizer; the grafting rate of the corresponding segment of SIS in the obtained compatibilizer is 40wt%, and the grafting rate of the corresponding grafted group of maleic anhydride is 48wt%.

[0099] Examples 1 to 9

[0100] A method for preparing a self-sealing adhesive comprises the following steps:

[0101] (1) placing natural rubber, nitrile rubber, SIS 4010, nano-silica rods, 3-(octanoylthio)propyltriethoxysilane (NXT), a compatibilizer, rice husk-derived white carbon black, graphene, hollow glass microspheres and paraffin oil in an internal mixer, and mixing them at 65° C. and 70 rpm for 5.5 min to obtain a first masterbatch;

[0102] (2) placing neodymium rare earth butadiene rubber NdBR-40, tert-butylphenol hydroxybenzoate (BHT), magnesium oxide, octanoic acid, sulfur IS, vulcanization accelerator TBzTD and DPG in an internal mixer, mixing at 55° C. and 40 rpm for 3 min to obtain a second masterbatch;

[0103] (3) placing the first masterbatch prepared in step (1), the second masterbatch prepared in step (3) and a xylene resin in a twin-screw extruder for mixed extrusion to obtain a mixed rubber material;

[0104] (4) placing the mixed rubber material obtained in step (2) in a vulcanizer and vulcanizing it at 140° C. and 7 MPa for 15 min to obtain a self-sealing rubber material.

[0105] Table 1

[0106]

[0107] Table 2

[0108]

[0109]

[0110] Example 10

[0111] The difference from Example 1 is that the amount of the compatibilizer is 5 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0112] Embodiment 11

[0113] The difference from Example 1 is that the amount of the compatibilizer is 15 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0114] Example 12

[0115] The difference from Example 1 is that the amount of the compatibilizer is 2 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0116] Embodiment 13

[0117] The difference from Example 1 is that the amount of nano-silica rods is 20 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0118] Embodiment 14

[0119] The difference from Example 1 is that the amount of nano-silica rods is 2 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0120] Examples 15 to 18

[0121] The difference from Example 1 is that the amounts of natural rubber, nitrile rubber and neodymium rare earth butadiene rubber are different. The specific amounts are shown in Table 3. The remaining components, amounts and preparation steps are the same as those in Example 1.

[0122] Table 3

[0123]

[0124] Embodiment 19

[0125] The difference from Example 1 is that the amount of sulfur used is 20 parts by weight, and the other components, amounts and preparation steps are the same as those in Example 1.

[0126] Embodiment 20

[0127] The difference from Example 1 is that the weight ratio of ethylene-ethyl acrylate copolymer (SK Group of South Korea, EEA6200), SIS (Sinopec Baling Petrochemical, 4010), maleic anhydride and dibenzoyl peroxide added to the compatibilizer used in this embodiment during the preparation process is 100:40:4:5, the grafting rate of the corresponding segment of SIS in the prepared compatibilizer is 40wt%, the grafting rate of the grafting group corresponding to maleic anhydride is 40wt%, and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0128] Embodiment 21

[0129] The difference from Example 1 is that the weight ratio of ethylene-ethyl acrylate copolymer (SK Group of South Korea, EEA6200), SIS (Sinopec Baling Petrochemical, 4010), maleic anhydride and dibenzoyl peroxide added to the compatibilizer used in this embodiment during the preparation process is 100:18:4:5, the grafting rate of the corresponding segment of SIS in the prepared compatibilizer is 20wt%, the grafting rate of the corresponding grafted group of maleic anhydride is 18wt%, and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0130] Comparative Example 1

[0131] The difference from Example 1 is that: in step (1), no nitrile rubber, SIS 4010 and compatibilizer are added, in step (2), no neodymium rare earth butadiene rubber is added, and the amounts of the remaining components are shown in Table 1; in step (1), the kneading temperature is 75° C., the rotation speed is 80 rpm, and the time is 6 min; in step (4), the vulcanization temperature is 170° C., and the time is 15 min; and the remaining steps are the same as in Example 1.

[0132] Comparative Example 2

[0133] The difference from Example 1 is that no nano-silica rods are added in step (1), and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0134] Comparative Example 3

[0135] The difference from Example 1 is that maleic anhydride grafted polyethylene (abbreviated as PE-g-MAH, source: Coase Chemical, model number W1H) is used to replace the compatibilizer in Example 1 in equal parts by weight, and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0136] Comparative Example 4

[0137] The difference from Example 1 is that no nitrile rubber is added in step (1), and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0138] Comparative Example 5

[0139] The difference from Example 1 is that SIS 4010 is replaced by an ethylene-octene copolymer (POE) in equal parts by weight, and the remaining components, amounts and preparation steps are the same as those in Example 1.

[0140] Comparative Example 6

[0141] The difference from Example 1 is that step (4) is omitted, and the performance test is directly performed on the mixed rubber material obtained in step (3).

[0142] The following performance tests were performed on the self-sealing rubber materials prepared in all the examples and comparative examples of the present application:

[0143] (1) Hardness: measured at 25°C using a Shore hardness tester (GT-GS-MB, Borui, Germany) according to the method in GB / T 531-1999;

[0144] (2) Glass transition temperature (Tg): DSC curves were measured using a heat flow differential scanning calorimeter (Mettler Toledo, Switzerland, 204F1), where the sample amount was 5 to 20 mg, the test temperature range was -100 to 150 °C, the heating rate was 20 °C / min, and the protective gas was nitrogen;

[0145] (3) Dynamic elastic modulus (E'): measured using a rubber processing analyzer (RPA-2000, Alpha Corporation, USA) at 5% dynamic strain, 10 Hz frequency, and 80 °C;

[0146] (4) Air tightness test: The self-sealing rubber materials prepared in all the embodiments and comparative examples of the present application are adhered to the inner wall of the airtight layer of a tire of the same specifications and the tire is inflated, and then the tire is punctured with an iron nail with a diameter of 4 mm; without pulling out the iron nail, the nailed part of the tire is immersed in soapy water to observe whether it leaks; the iron nail is pulled out, and then the nailed part is immersed in soapy water in the same manner to observe whether it leaks; after standing for 48 hours, the nailed part is immersed in soapy water again in the same manner to observe whether it leaks.

[0147] The test results are shown in Table 4. The left side of the glass transition temperature (Tg) is the Tg of the rubber component, and the right side is the Tg of the resin component, expressed as Tg (rubber component) / Tg (resin component). The smaller the difference between the two, the better the compatibility.

[0148] Table 4

[0149]

[0150] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0151] Compared with Example 1, Comparative Example 1 does not contain nitrile rubber, thermoplastic elastomer SIS 4010, compatibilizer and neodymium rare earth butadiene rubber in its raw materials, and its rubber system is only natural rubber. Therefore, the glass transition temperature of Comparative Example 1 is lower than that of Example 1, but the hardness and dynamic elastic modulus of Comparative Example 1 are greater than those of Example 1. It can be seen that its rigidity is too strong, resulting in poor adhesion, and it is easy to be thrown out when the tire rotates at high speed, thereby causing a potential driving safety hazard.

[0152] By comparing Example 1 with Comparative Examples 1 to 5, it can be seen that the use of a specific type of compatibilizer in the present application can improve the compatibility of the components in the self-sealing rubber composition, better exert the synergistic effect of the components, and improve the processability of the self-sealing rubber composition; introducing a compatibilizer having a specific structure in the present application into the self-sealing rubber composition can realize the construction of a network structure in the self-sealing rubber composition, thereby improving the structural stability and air tightness of the prepared self-sealing rubber; at the same time, the compounding of a specific type of first rubber, second rubber, third rubber and thermoplastic elastomer in the self-sealing rubber composition of the present application can improve the high and low temperature resistance of the self-sealing rubber; introducing nano-silica rods into the self-sealing rubber composition can exert its reinforcing The self-sealing rubber composition can improve the stability of the self-sealing rubber composition under high temperature and high pressure environment in the tire, and inhibit the self-sealing rubber from flowing under high temperature or high-speed rotation of the tire, thereby improving the driving safety of the car; the self-sealing rubber prepared from the above-mentioned self-sealing rubber composition of the present application has good structural stability and air tightness, and is not easy to flow inside the tire due to local heat accumulation; when the self-sealing rubber prepared from the rubber composition provided by the present application is used as a self-sealing agent in the tire, after the tire is punctured by a foreign object, it can quickly wrap the punctured part to inhibit tire leakage, and when the foreign object is pulled out, the self-sealing rubber can quickly flow under the action of the air pressure in the tire to block the puncture, thereby inhibiting the occurrence of slow tire leakage or tire blowout.

[0153] By comparing Example 1 and Comparative Example 6, it can be seen that by adopting the preparation method of the self-sealing rubber compound mentioned above in the present application, a more stable cross-linked network structure can be obtained, thereby improving the stability and air tightness of the self-sealing rubber compound, and making it less likely to flow inside the tire due to local heat accumulation.

[0154] By comparing Examples 1, 10 to 12, it can be seen that limiting the weight fraction of the compatibilizer within the above-mentioned range of the present application is beneficial to improving the compatibility of the components in the self-sealing adhesive composition, and is beneficial to better exerting the synergistic effect of the components, thereby helping to improve the structural stability and air tightness of the prepared self-sealing adhesive.

[0155] By comparing Examples 1, 13 and 14, it can be seen that limiting the weight fraction of the nano-silica rods within the above-mentioned range of the present application is conducive to better exerting the reinforcing effect of the silica rods, thereby helping to improve the stability of the self-sealing rubber composition under high temperature and high pressure environment in the tire, and helping to inhibit the flow of the self-sealing rubber at high temperature or high-speed rotation of the tire, thereby improving the driving safety of the vehicle.

[0156] By comparing Examples 1, 15 to 18, it can be seen that the weight percentages of the first rubber, the second rubber and the third rubber include but are not limited to the above ranges, and limiting them within the above ranges is conducive to exerting their synergistic effect, thereby facilitating improving the high and low temperature resistance and air tightness of the self-sealing rubber.

[0157] By comparing Examples 1 and 19, it can be seen that the weight fraction of the vulcanizing agent includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the vulcanization efficiency, and is beneficial to improving the structural stability of the self-sealing rubber material obtained by vulcanization, thereby helping to improve its self-sealing performance.

[0158] By comparing Examples 1, 20 and 21, it can be seen that, compared with other ranges, limiting the grafting rate of the chain segment corresponding to the second styrene-isoprene-styrene block copolymer in the compatibilizer and the grafting rate of the grafting group corresponding to maleic anhydride within the above-mentioned range of the present application is beneficial to improving the compatibility of the compatibility of the compatibilizer, thereby improving the compatibility of the components, better exerting the synergistic effect of the components, improving the processability of the self-sealing adhesive composition, and forming a structurally stable physical cross-linked network structure, thereby improving the structural stability and air tightness of the self-sealing adhesive and improving its self-sealing performance.

[0159] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0160] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A self-sealing adhesive composition, characterized in that: The self-sealing rubber composition comprises: a first rubber, a second rubber, a third rubber, a thermoplastic elastomer, a nano-silica rod, a silane coupling agent and a compatibilizer; wherein the first rubber is selected from natural rubber and / or polyisoprene rubber, the second rubber is nitrile rubber, and the third rubber is rare earth butadiene rubber; the compatibilizer is a modified ethylene-ethyl acrylate copolymer, and the modified ethylene-ethyl acrylate copolymer is obtained by reacting a first styrene-isoprene-styrene block copolymer, maleic anhydride and ethylene-ethyl acrylate copolymer under the action of an initiator; and the thermoplastic elastomer is a second styrene-isoprene-styrene block copolymer.

2. The self-sealing adhesive composition according to claim 1, characterized in that: The self-sealing rubber composition comprises, by weight: 20 to 50 parts of the first rubber, 20 to 50 parts of the second rubber, 20 to 50 parts of the third rubber, 10 to 30 parts of the thermoplastic elastomer, 5 to 20 parts of the nano-silica rods, 1 to 10 parts of the silane coupling agent and 5 to 15 parts of the compatibilizer; Preferably, the self-sealing rubber composition comprises, by weight: 30 to 50 parts of the first rubber, 20 to 30 parts of the second rubber, 20 to 30 parts of the third rubber, 10 to 20 parts of the thermoplastic elastomer, 15 to 20 parts of the nano-silica rods, 1 to 5 parts of the silane coupling agent and 5 to 10 parts of the compatibilizer.

3. The self-sealing adhesive composition according to claim 1, characterized in that: The ethylene-ethyl acrylate copolymer has a structure shown in formula (I): Wherein, R1 is selected from vinylene, propenylene or C2-C6 straight-chain alkylene; R2 is selected from C2-C5 straight-chain alkylene; x is any integer from 10 to 30, and y is any integer from 10 to 30; Preferably, in the compatibilizer, the corresponding segment of the first styrene-isoprene-styrene block copolymer includes a first styrene repeating unit and a first isoprene repeating unit, preferably the weight ratio of the first styrene repeating unit to the first isoprene repeating unit is (10-50):(50-90), more preferably the weight average molecular weight of the corresponding segment of the first styrene-isoprene-styrene block copolymer in the compatibilizer is 25,000-28,000; Preferably, in the compatibilizer, the grafting rate of the corresponding segment of the first styrene-isoprene-styrene block copolymer is 40-60wt%, and the grafting rate of the corresponding grafting group of the maleic anhydride is 40-60wt%; Preferably, the weight ratio of the ethylene-ethyl acrylate copolymer, the first styrene-isoprene-styrene block copolymer, the maleic anhydride and the initiator is (95-120):(32-62):(1-9):(3-13).

4. The self-sealing adhesive composition according to any one of claims 1 to 3, characterized in that: In the thermoplastic elastomer, the second styrene-isoprene-styrene block copolymer comprises a second styrene repeating unit and a second isoprene repeating unit, and preferably the weight ratio of the second styrene repeating unit to the second isoprene repeating unit is (10-40):(60-90); Preferably, the weight average molecular weight of the thermoplastic elastomer is 80,000 to 120,000; Preferably, the thermoplastic elastomer is selected from one or more of SIS1105, SIS1106, SIS 4010 and SIS 4019; Preferably, the first rubber is natural rubber, preferably the natural rubber is cis-1,4-polyisoprene, more preferably the weight average molecular weight of the cis-1,4-polyisoprene is 400,000 to 3,000,000, and the weight percentage of the cis structure thereof is ≥97wt%; Preferably, the glass transition temperature of the nitrile rubber is ≤-50°C, more preferably -60 to -55°C; Preferably, the weight percentage of acrylonitrile monomer in the nitrile rubber is 20 to 50 wt %; preferably, the Mooney viscosity of the nitrile rubber at 100° C. is 50 to 75; Preferably, the rare earth butadiene rubber is a neodymium rare earth butadiene rubber, and preferably the neodymium rare earth butadiene rubber has a weight average molecular weight of 800,000 to 900,000, a number average molecular weight of 200,000 to 300,000, and a relative molecular mass distribution of 3.0 to 4.5; Preferably, the aspect ratio of the nano-silica rod is (50-500):(1-50), more preferably the diameter is 5-25 nm and the length is 80-100 nm; Preferably, the silane coupling agent is selected from one or more of thiocarboxyl silane, vinyl silane, epoxy silane and methacryloxy silane; more preferably, the silane coupling agent is selected from one or more of 3-(octanoylthio)propyltriethoxysilane, 3-propionylthio-1-propyltriethoxysilane, vinyltrimethoxysilane and 3-(methacryloyloxy)propyltrimethoxysilane.

5. The self-sealing adhesive composition according to claim 4, characterized in that: The self-sealing adhesive composition further comprises: a filler, a plasticizer, an antioxidant, an activator and a tackifying resin; Preferably, the self-sealing adhesive composition further comprises, by weight: 5 to 20 parts of the filler, 20 to 60 parts of the plasticizer, 1 to 5 parts of the antioxidant, 2 to 8 parts of the activator and 5 to 50 parts of the tackifying resin; Preferably, the self-sealing adhesive composition further comprises, by weight: 10 to 15 parts of the filler, 30 to 40 parts of the plasticizer, 2 to 3 parts of the antioxidant, 2 to 5 parts of the activator and 10 to 30 parts of the tackifying resin; Preferably, the filler is selected from one or more of white carbon black, graphene, hollow glass microspheres and clay, and preferably the filler is a combination of rice husk-derived white carbon black, graphene and hollow glass microspheres; more preferably, the pH value of the rice husk-derived white carbon black is 5 to 7, and the nitrogen adsorption specific surface area is 150 to 175 m 2 / g, the adsorption specific surface area of ​​hexadecyltrimethylammonium bromide is 130~165m 2 / g; more preferably, the mesh number of the graphene is 50-600 meshes, and the thermal conductivity is 600-3500W / mK; more preferably, the material of the hollow glass microspheres is borosilicate, and the average particle size is 10-250μm, and the wall thickness is 1-2μm; Preferably, the plasticizer is selected from one or more of paraffin, paraffin oil, coal tar, coumarone resin, environmentally friendly aromatic oil, and cyclohexane oil. Preferably, the plasticizer is paraffin oil, and more preferably, the paraffin oil has a density of 0.75 to 0.95 g / mL at 20°C and a flash point of 120 to 200°C. Preferably, the antioxidant is selected from one or more of tert-butylphenol hydroxybenzoate, p-hydroxybenzoate and tri-tert-butylhydroxybenzoate; Preferably, the activator is selected from an inorganic activator and / or an organic activator, preferably the inorganic activator is selected from one or more of zinc oxide, calcium oxide, magnesium oxide and lead oxide, and preferably the organic activator is selected from one or more of stearic acid, octanoic acid, zinc stearate and ethanolamine; Preferably, the tackifying resin is selected from gum rosin and / or xylene resin.

6. The self-sealing adhesive composition according to any one of claims 1 to 5, characterized in that: The self-sealing rubber composition further comprises: a vulcanizing agent and a vulcanization accelerator; Preferably, the self-sealing adhesive composition further comprises, by weight: 0.01 to 10 parts of the vulcanizing agent and 0.01 to 10 parts of the vulcanization accelerator, preferably 0.1 to 0.3 parts of the vulcanizing agent and 0.1 to 0.2 parts of the vulcanization accelerator; Preferably, the vulcanizing agent is sulfur; Preferably, the vulcanization accelerator is selected from thiuram vulcanization accelerators and / or guanidine vulcanization accelerators; More preferably, the thiuram vulcanization accelerator is selected from one or more of tetramethylthiuram monosulfide, tetraisobutylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabenzylthiuram disulfide, methylphenylthiuram disulfide and bis(1,5-pentylene)thiuram tetrasulfide; More preferably, the guanidine vulcanization accelerator is selected from one or more of diphenylguanidine, di-o-tolylguanidine and o-tolylbiguanide; More preferably, the vulcanization accelerator is a combination of a thiuram vulcanization accelerator and a guanidine vulcanization accelerator, and the weight ratio of the two is (0.5-1.5):(0.1-1).

7. A self-sealing rubber compound, characterized in that: The self-sealing rubber material is prepared by mixing and vulcanizing the self-sealing rubber material composition according to claim 6.

8. A method for preparing the self-sealing adhesive according to claim 7, characterized in that: The preparation method comprises: Step S1, kneading the first rubber, the second rubber, the thermoplastic elastomer, the nano-silica rods, the silane coupling agent and the compatibilizer to obtain a first masterbatch; Step S2, mixing the third rubber with a vulcanizing agent to obtain a second masterbatch; Step S3, co-extruding the first masterbatch and the second masterbatch to obtain a mixed rubber material; Step S4, vulcanizing the mixed rubber material to obtain the self-sealing rubber material.

9. The method for preparing the self-sealing adhesive according to claim 8, characterized in that: In step S1, the banburying temperature is 60-80°C and the time is 5-9 minutes; Preferably, stirring is performed during the banburying process, and more preferably, the stirring rate is 60 to 100 rpm; Preferably, in step S4, the vulcanization temperature is 100-180°C, the pressure is 5-10 MPa, and the time is 3-20 min; Preferably, fillers and plasticizers are also added in step S1; Preferably, in step S2, the mixing temperature is 40-60°C and the mixing time is 3-5 minutes; Preferably, stirring is performed during the mixing process, and more preferably, the stirring rate is 40 to 100 rpm; Preferably, an activator, an antioxidant and a vulcanization accelerator are also added in step S2; Preferably, a tackifier is also added in step S3.

10. Use of the self-sealing rubber composition according to any one of claims 1 to 6 or the self-sealing rubber according to claim 7 in the field of tires.

Citation Information

Patent Citations

  • Sealant rubber composition for inner tire surface and sealant-coated tire

    CN113631647A